Association of Protective HLA-A With HLA-B∗27 Positive Ankylosing Spondylitis - Nordin, Jessika; Pettersson, Mats; Rosenberg, Lina Hultin; Mathioudaki, Argyri; Karlsson, Åsa; Murén, Eva; Tandre, Karolina; Rönnblom, Lars; Kastbom, Alf; Cedergren, Jan; Eriksson, Per; Söderkvist, Peter; et al. (Frontiers in Genetics, 2021)
Objectives To further elucidate the role of the MHC in ankylosing spondylitis by typing 17 genes, searching for HLA-B∗27 independent associations and assessing the impact of sex on this male biased disease. Methods High-confidence two-field resolution genotyping was performed on 310 cases and 2196 controls using an n-1 concordance method. Protein-coding variants were called from next-generation sequencing reads using up to four software programs and the consensus result recorded. Logistic regression tests were applied to the dataset as a whole, and also in stratified sets based on sex or HLA-B∗27 status. The amino acids driving association were also examined. Results Twenty-five HLA protein-coding variants were significantly associated to disease in the population. Three novel protective associations were found in a HLA-B∗27 positive population, HLA-A∗24:02 (OR = 0.4, CI = 0.2–0.7), and HLA-A amino acids Leu95 and Gln156. We identified a key set of seven loci that were common to both sexes, and robust to change in sample size. Stratifying by sex uncovered three novel risk variants restricted to the female population (HLA-DQA1∗04.01, -DQB1∗04:02, -DRB1∗08:01; OR = 2.4–3.1). We also uncovered a set of neutral variants in the female population, which in turn conferred strong effects in the male set, highlighting how population composition can lead to the masking of true associations. Conclusion Population stratification allowed for a nuanced investigation into the tightly linked MHC region, revealing novel HLA-B∗27 signals as well as replicating previous HLA-B∗27 dependent results. This dissection of signals may help to elucidate sex biased disease predisposition and clinical progression.